ACE-I und ARB bei chronischen Nierenerkrankungen: Was muss ich berücksichtigen? = ACE Inhibitors and ARB in chronic kidney disease : what has to be considered - Zeier, Martin (Deutsche medizinische Wochenschrift, 2018)
Proteinuric kidney disease, especially in the early and middle stages of renal insufficiency, may be favorably affected by ACE-I/ARB. The progression of renal insufficiency is thereby slowed down and dialysis obligation occurs later or can even be avoided. This effect is independent of the underlying glomerular kidney disease. In the advanced stage of renal insufficiency, the benefit of ACE-I/ARB cannot yet be conclusively assessed. The interruption of ACE-I/ARB therapy may possibly contribute to a certain recovery of renal function and delay the onset of dialysis a little. However, studies are still pending and the benefits of ACE-I/ARB for the heart and blood vessels, especially at this stage of renal insufficiency, should not be overlooked. Patients with proteinuria benefit from ACE-I/ARB not only in terms of renal stabilization. A cardio-protective effect by reduction of proteinuria and a delay of progression is proven. On the other hand, the protective effect of ACE-I/ARB that can be detected directly on the heart and blood vessels should not be disregarded. Thus, even if chronic renal insufficiency no longer benefits directly from ACE-I/ARB therapy, cardiac protection may still be of great importance to the chronic kidney patient.